Impact of National Antibiotic Guideline Implementation on Meropenem Utilization in a Teaching Hospital in Bengkulu, Indonesia - Yusna Fadliyyah Apriyanti; Susi Delvera; Bella Donna Perdana Putra (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
The World Health Organization (WHO) classified antibiotics into the AWaRe categories to encourage rational prescribing and reduce inappropriate use of broad-spectrum agents. Indonesia adopted this framework through the National Antibiotic Guideline outlined in Ministry of Health Regulation No. 28/2021, which strengthened antimicrobial stewardship (AMS) efforts in hospitals. Although WHO categorized meropenem in the Watch group, the national guideline reclassified it as a Reserve antibiotic, highlighting its critical role as a last-line treatment for multidrug-resistant infections and the need for strict oversight. This study aimed to evaluate the impact of the guideline’s implementation on meropenem utilization in a teaching hospital and assess its position within the Drug Utilization 90% (DU90%) segment from 2020 to 2022. Using a cross-sectional design, aggregated inpatient antibiotic consumption data were analyzed across pre-intervention (May 2020–August 2021) and post-intervention (September 2021–December 2022) periods. Antibiotic use was quantified using Defined Daily Doses per 100 patient-days (DDD/100 PD) according to the ATC/DDD methodology, and DU90% analysis was applied to identify antibiotics accounting for 90% of total consumption. Meropenem showed a significant 43% reduction in the DDD/100 PD score during the post-intervention period (t = 4.427; p < 0.05), suggesting that the guideline contributed to a more controlled, optimized use of this high-priority antibiotic. However, meropenem consistently remained within the DU90% segment throughout the three years, indicating that despite reduced utilization, it continued to account for a substantial proportion of antibiotic use in the hospital. These findings underscored the importance of sustained AMS implementation and strict regulatory adherence to preserve meropenem effectiveness and mitigate the risk of antimicrobial resistance.